Blob tracking and formation in edge and SOL plasmas using Q-factor. (1st November 2022) - Bisai, N; Sen, A
Abstract: We propose a direct means of identifying and tracking plasma blobs in the tokamak edge and scrape-off layer (SOL) regions through evaluation of a quantity Q that is a measure of the relative contribution from the square of the sheared strain and the square of the vorticity at any spatial location. The sheared strain and vorticity are related to the various velocity gradients in the plasma fluid. The blob formation from the breakup of a streamer structure can be determined from the criterion Q  > 0. A blob is associated with a high negative value of Q that is indicative of a stable vortex flow of the local fluid trajectories. The validity of this criterion, obtained from a linear eigenvalue analysis of the stability of fluid trajectories, is supported by nonlinear fluid simulations that clearly identify blobs with regions where Q  < 0 and exceeds a threshold value. The parameter Q can be experimentally determined from measurements of local electric field shears using gas puff imaging or Langmuir probe techniques, and the proposed criterion can provide a direct means of tracking plasma blobs. The rotation or spin of a blob in the edge and SOL regions can also be characterized by Q .